A review of flywheel energy storage systems: state of the art and opportunities. (February 2022) - Li, Xiaojun; Palazzolo, Alan
Abstract: Thanks to the unique advantages such as long life cycles, high power density, minimal environmental impact, and high power quality such as fast response and voltage stability, the flywheel/kinetic energy storage system (FESS) is gaining attention recently. There is noticeable progress in FESS, especially in utility, large-scale deployment for the electrical grid, and renewable energy applications. This paper gives a review of the recent developments in FESS technologies. Due to the highly interdisciplinary nature of FESSs, we survey different design approaches, choices of subsystems, and the effects on performance, cost, and applications. This review focuses on the state of the art of FESS technologies, especially those commissioned or prototyped. We also highlighted the opportunities and potential directions for the future development of FESS technologies. Highlights: A review of the recent development in flywheel energy storage technologies, both in academia and industry. Focuses on the systems that have been commissioned or prototyped. Different design approaches, choices of subsystems, and their effects on performance, cost, and applications. Opportunities and potential directions for the future development of flywheel energy storage technologies.